GPS Anti-Jamming Technique Using Smart Antenna Systems - Akobundu, G.C.; Gbenga-Ilori, A.O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper presents a global positioning system (GPS) anti-jamming technique using a smart antenna system. In anti-jamming systems, adaptive array antennas are used to estimate the direction of signals arriving at the antenna and spatially filter the desired signal from the unwanted signals by adaptively controlling the direction of the maximum radiated beam. In this study, the uniform linear array was used for the smart antenna configuration. The work compared the performance of non-blind adaptive algorithms with blind algorithms for adaptive beamforming. Non-blind adaptive algorithm using least mean square (LMS) algorithm and blind algorithm using constant modulus algorithm (CMA) was studied and implemented for adaptive beamforming while estimation of signal parameters via rotational invariance technique (ESPRIT) and multiple signal classification (MUSIC) algorithms were implemented for the direction of arrival (DOA) estimation. The effect of varying the number of elements in the antenna array and the required spacing between them was also investigated. Results of comparison carried out using numerical analysis showed that both algorithms performed well for the DOA estimation, with MUSIC algorithm producing a better direction of arrival spectrum with little or no minor peaks. For the beamforming, both LMS and CMA produced maximum radiation in the direction of the desired signal. LMS placed deeper nulls in the directions of interference with faster convergence and fewer errors as compared with CMA that presented errors and was able to suppress the interference to a minimal extent. It was also shown that as the number of elements in the array increases, a more directive beam and DOA spectrum is produced.